Cardiac involvement in Dutch patients with sarcoglycanopathy: A cross‐sectional cohort and follow‐up study. Issue 6 (December 2014) - Schade van Westrum, Steven M.; Dekker, Lukas R.C.; de Voogt, Willem G.; Wilde, Arthur A.M.; Ginjaar, Ieke B.; de Visser, Marianne; van der Kooi, Anneke J.
ABSTRACT Introduction: The aim of this study is to describe the frequency, nature, severity, and progression of cardiac abnormalities in a cohort of Dutch sarcoglycanopathy patients. Methods: In this cross‐sectional cohort study, patients were interviewed using a standardized questionnaire and assigned a functional score. Electrocardiography (ECG), echocardiography, and 24‐h ECG were performed. Results: Twenty‐four patients with sarcoglycanopathy had a median age of 25 years (range, 8–59 years). Beta blockers were used by 13%, and 17% used angiotensin‐converting enzyme inhibitors. ECG abnormalities were present in 5 (21%), and 4 (17%) fulfilled the criteria for dilated cardiomyopathy (DCM). There were no significant differences in median age or severity of disease between patients with or without DCM. Eleven patients were examined earlier. Median follow‐up time was 10 years. Two of the 11 patients (18%) developed DCM during follow‐up. Conclusions: Seventeen percent of the patients with sarcoglycanopathy were found to have dilated cardiomyopathy. We recommend biannual cardiac monitoring, including ECG and echocardiography. Muscle Nerve50: 909–913, 2014